Pengembangan Media Papan Hitung Untuk Meningkatkan Hasil Belajar Materi Operasi Hitung Penjumlahan Siswa Madrasah Ibtidaiyah - Fina Atifatul Husna; Nadlir (JRPM (Jurnal Review Pembelajaran Matematika), 2023)
The use of mathematics learning media in the lower class is necessary because low-class students are not yet able to think abstractly, which is a need for visualization in reals form. The purpose of this study was to improve student learning outcomes in addition to calculation operations with the help of counting board media. The development model used is the ADDIE model, with the sample being 20 students in grade 1. Data collection techniques used questionnaires, interviews, observations, tests, and documentation. The results of this validation related to the feasibility of design experts amounting to 88.33% including a very feasible category, material experts amounting to 84.17% including a feasible category, and learning experts amounting to 92.5% including a very feasible category. Then the results of the field trial obtained an N-Gain value of 0.73 which is included in the high category. So that the development of the counting board media can improve student learning outcomes in addition to operation material for MINU Unggulan Wali Songo Bojonegoro students.